An Analysis on Gen Z Employees’ Job Engagement and Attitude towards Work w0ith Special Reference to IT Industry - M. Pavithra; Dr. G. Bala Murugan (International Journal of Engineering and Management Research, 2023)
Generation Z, as known or named at another time or place the "Zoomers," is the mathematical disciple following the Millennials. Born betwixt the intervening-1990s and the early 2010s, Gen Z is the first production to have adult completely in the mathematical age. As a result, they are famous for being type of educational institution-savvy and very affiliated. Gen Z is still a different and politically intentional production, accompanying a powerful desire for genuineness and transparency in the guests and brands they support. This abstract supports a brief survey of the traits and principles of Gen Z, emphasize their singular view on the globe and their affect humankind and sophistication.